Charles B. Elliott papers - Elliott, Charles B. (Charles Burke), 1861-1935.
Diaries, letterbook, newspaper clippings, and English translations of Philippine newspaper articles written in Spanish and Filipino. Documents Elliott's service as associate justice of the Philippine Supreme Court, 1910-1911, and as secretary of commerce and police of the second Philippine Commission (1900-1916). Subjects include social, political, and governmental affairs in the Philippines; and Elliott's travels in the Philippines and China.
Jurist, lawyer, author, associate justice of the Supreme Court of the Philippines, and secretary of police and commerce.
Collection material in English, with Filipino and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Philippines. -- Supreme Court; United States. -- Philippine Commission (1900-1916); Courts -- Philippines; Police administration -- Philippines; China -- Description and travel; Philippines -- Newspapers; Philippines -- Commerce; Philippines -- Description and travel; Philippines -- History -- 1898-1946.; Philippines -- Politics and government -- 1898-1935.; Philippines -- Social conditions -- 20th century; Public officials -- Philippines